Gambaran Pola Makan dan Status Gizi pada Remaja Putri di Pondok Pesantren As’ad Kota Jambi - Aisah, Aisah; Kurnia, Fitrian (3031-8572, 2024)
Nutritional status is the determinant of everything related to nutritional resources. Development resources such as poor nutrition, especially for children, which can reduce the potential of community development resources. Human resources are the Human Development Index (HDI) which has three main factors that are most important, namely education, health and economy. These three factors are closely related to the nutritional status of the community. The results of the 2018 Riskesdas, the prevalence of obesity in Indonesia was 21.8% at 34.1%, the highest in North Sulawesi (30.2%%), while the lowest in East Nusa Tenggara was (10.3. The prevalence of obesity in Jambi Province according to the 2018 Riskesdas was 19.83%. Eating patterns show the culture, habits and beliefs of a particular community group. This causes one group to be different from another group. The population in this study were 265 female students at the Sa'ad Islamic Boarding School in Jambi City, with a sample size of 80 female students. The results of the initial survey in August 2023 at the Sa'ad Islamic Boarding School through direct interviews with 10 female students, 7 of whom had symptoms of anemia such as lack of concentration while studying, fatigue, shortness of breath and a pale face. looks paleKnowing the Picture of Eating Patterns with the Incident of Adolescent Girls at the Sa'ad Islamic Boarding School in Jambi City. the majority of respondents were 16 years old with the number of respondents being 34 female students (50.7%). The majority of respondents were in grade XI with the number of respondents being 35 female students (52.3%). There were 35 respondents (52.2%) experiencing poor nutritional status, while respondents who had good nutritional status were 32 respondents (47%). most respondents had a good diet, namely 41 female students (61.2%).